Coordination complexes of slight tetrylene with platinum(II)‐8‐hydroxyquinolines: Structure and bonding analysis. Issue 3 (24th June 2020) - Loan, Huynh Thi Phuong; Van Duc, Hoang; Quy, Phan Tu; Thuy, Bui Thi Phuong; Van Tat, Pham; Quang, Duong Tuan; Nhung, Nguyen Thi Ai
Abstract: The structure and bonding situation in platinum complexes containing slight tetrylene ligands [PtCl‐C9 H6 NO‐NHE] (Pt‐NHE) with E = C, Si, Ge were examined by DFT calculations with the levels are BP86/def2‐SVP and BP86/def2‐TZVPP. The predicted equilibrium structure of the ligands NHE in Pt‐NHE are bonded in distorted end‐on way to PtCl‐8‐hydroxyquinolines fragment with the bending angle, α, exhibits the biggest value in carbenes systems then slightly decrease from Pt‐NHC to Pt‐NHGe . Bond dissociation energies (BDEs), D e (kcal.mol ‐1 ), decrease from the carbene complex to the weaker bonded silylene and germylene manners. The BDE when considering dispersion correction at the BP86‐D3(BJ)/def2‐TZVPP level confirms that Pt‐E bond in Pt‐NHE belongs to the effect of the bulky group in slight tetrylene NHE and Pt(II)‐group fragment which makes the intrinsic Pt‐E bond strength decreases from carbene to germylene complexes. The hybridization of atoms E and Pt have large p characters while the hybridization of atom Pt has greater d character which lead to the Pt‐E bond possesses not only NHE→PtCl‐C9 H6 NO strong σ‐donation but also a significant contribution π‐donation NHE→PtCl‐C9 H6 NO and weak π‐backdonation metal‐ligand NHE←PtCl‐C9 H6 NO in complexes Pt‐NHE .